Political competitiveness and voters behavior : An exploratory study on socioeconomic issues - Munira, Abdul Razak; Muhammad Nubli, Abdul Wahab; Ahmad Fazullah, Ahmad Zainal Abidin; Noradilah, Md Nordin; Wan Marzuki, Wan Ismail; Mohd Iszuani, Mohd Hassan; Imaduddin, Abidin; Anita, Abdul Rani; Mansor, Mohd Noor; Ummi Munirah Syuhada, Mohamad Zan; Ahmad Zul Hakimi, Hassim (2015)
This study examined the causal relationship of political competitiveness and voters’ behavior in Malaysia. Questionnaires were developed and distributed to 14 f panel groups which involved 740 respondents in the age of 21-60 years old. The data collected from a survey was analyzed using SPSS 22 with descriptive statistical analysis to analyze the theory. From the result it can be found that both the political competitiveness and the voters’ behavior are influenced by the parties and candidate capabilities to handle electoral issues. This study paved the way on empowering political parties and candidates as well as to enhance the political competitiveness quality in Malaysia.